NBCA-Lipiodol Mixture Embolization of Persistent Urine Leakage After Orthotopic Neobladder Formation: Techniques and Outcomes - Han, Jang Hee; Yuk, Hyeong Dong; Choi, Jin Woo; Ku, Ja Hyeon (Frontiers in Surgery, 2022)
Objective: To show the effective and successful technical approach of percutaneous embolization for persistent urine leakage that occurred after orthotopic neobladder formation. Materials and Methods: We retrospectively reviewed patients who underwent percutaneous embolization of N-butyl cyanoacrylate (NBCA) and lipiodol mixture after orthotopic neobladder formation at the Seoul National University Hospital (Seoul, Korea) from 1 January 2018 to 31 December 2020. Results: Among total of 182 patients of neobladder formation, 5 patients (4 males and 1 female) were enrolled in this study, and their median age was 61.0 years (interquartile range (IQR): 42.5-69.5 years). All the patients showed persistent urine leakage at the neobladder-urethral anastomosis site and percutaneous drainage was primarily performed. The median time to perform percutaneous embolization was 40 days (IQR: 31.5-71.5 days) postoperatively. Elective two-staged embolization was performed in three cases for large diameter with a large fluid-filled cavity, while re-embolization was needed for delayed recurrence of urine leakage in two cases. Complete resolution of urine leakage was seen in all the cases and the median time to leakage closure was 55 days (IQR: 27.5-82.5 days). The median follow-up period after leakage closure was 26 months (IQR: 15.5-36.4 months), and embolization material-related bladder stone was a noticeable complication (2 cases) during follow-up, which was removed endoscopically within one year after embolization. All patients’ quality of life (EQ-5D-5L score) was well maintained during the entire period. Conclusions: Persistent urine leakage after neobladder formation can be effectively managed with percutaneous embolization of “dumbbell technique” by reinforcing the closure of leakage tract from inner opening to the outer opening even for large diameter (>1cm).